TRANSFORMATION OF THE “CHILDREN’S WORLD” DURING THE OCCUPATION OF PART OF THE NORTH OSSETIAN ASSR - Hubulova, Svetlana Alekseevna (History, Archeology and Ethnography of the Caucasus, 2021)
Interest in the history of the Great Patriotic War is constantly increasing, while the research field is also expanding, covering those issues that have been previously unexplored. Until recently, such a “forbidden” subject was the everyday life of the population during the Nazi occupation. The paper attempts to shed light on the issue of children’s perception of the enemy and their aggressive policy, as well as children’s conduct in the conditions of the Nazi’s occupation of part of the territory of North Ossetian ASSR. Children, like all adults, endured hardships of war, complicated by the occupation regime of the fascist army. We introduce new materials of the Extraordinary State Commission for the Establishment and Investigation of the Atrocities of the German Fascist Invaders and Their Accomplices and the Damage They Caused (ChGK) on the territory of the North Ossetian ASSR, in which testimonies of children are recorded. The materials on the settlements of Alagir, Mozdok, Digora and Ardon, as well as the villages most affected by the occupation, were selected as reference materials. Recollections-interviews of 2000s, as another type of ego-documents, have been analyzed. The study was conducted with the use of the following methods: problem-chronological (the obtained material was analyzed according to the selected problems), anthropologically oriented (made it possible to take into account the age, psychological, status characteristics of children), comparative-historical (the problems identified in the memories were compared among different regions), systemic-structural (the main problems in children’s perception of military reality were highlighted) methods and means of content analysis, microhistory (allowed us to consider the child’s everyday practices) and interviewing. Thanks to the methods applied, it became possible to reconstruct the world of a wartime childhood. The analysis shows the degree of information content, reliability of the identified ego-documents. It has been revealed that the evidence taken in 1943-1944 is more objective than the memories recorded many years later. In the latter case, great emotionality is noted. However, the people’s recollections are fragmentary: they mainly consist of everyday hardships, problems, and only in some cases – the most vivid memories. The degree of their representativeness is inferior to the evidence taken directly after the events. Nonetheless, all documents related to children’s perception of the occupation make it possible to supplement the history of the war on a regional scale. The testimonies of the “little man”, whose children’s world was disturbed and traumatized, are of great importance for filling the scientific gaps in the history of the Great Patriotic War.